Cognitive performance associated with self-care activities in mexican adults with type 2 diabetes - Compeán Ortiz, Lidia Guadalupe; Gallegos Cabriales, Esther Carlota; González González, José Gerardo; Gómez Meza, Marco Vinicio; Therrien, Barbara; Salazar González, Bertha Cecilia (2010)
The purpose of this study was to determine the effect of memory-learning on self-care activities in adults with type 2 diabetes moderated by previous education/understanding in diabetes and to explore the explicative capacity of age, gender, schooling, diabetes duration, and glycemic control in memory-learning. METHODS: A descriptive correlational study was conducted in a randomized sample of 105 Mexican adult patients with type 2 diabetes at a community-based outpatient clinic. Evaluation measures included the Wechsler Memory Scale for memory-learning; 2 questionnaires for self-care activities and previous education/understanding in diabetes, respectively; and glycosylated hemoglobin for glycemic control. Multiple linear regression analysis was used to examine the effect of memory-learning on self-care activities and the moderator capacity of previous education/understanding on diabetes. Multivariate analysis was used to identify the capacity of age, schooling, diabetes duration, and glycemic control in memory-learning types. RESULTS: A significant positive effect of memory-learning on self-care activities was found. Education/understanding in diabetes moderated the relationship between immediate and delayed memory-learning and self-care in glucose monitoring and diet. Gender, schooling, and the gender-glycemic control interaction explained memory-learning performance. CONCLUSIONS: Immediate and delayed verbal and visual memory-learning were important for the patient to carry out self-care activities, and this relationship can be moderated by previous education/understanding in diabetes. These findings suggest potential benefits in emphasizing cognitive strategies to promote relearning of self-care behaviors in persons who live with diabetes.